Preventive Effect of Lactobacillus helveticus SBT2171 on Collagen-Induced Arthritis in Mice - Yamashita, Maya; Matsumoto, Kurumi; Endo, Tsutomu; Ukibe, Ken; Hosoya, Tomohiro; Matsubara, Yumi; Nakagawa, Hisako; Sakai, Fumihiko; Miyazaki, Tadaaki (Frontiers in Microbiology, 2017)
We recently reported that the intraperitoneal inoculation of Lactobacillus helveticus SBT2171 inhibited the development of collagen-induced arthritis (CIA), a murine model of rheumatoid arthritis (RA). In the present study, we evaluated the effect of the oral administration of L. helveticus SBT2171 on CIA development and on the regulation of antigen-specific antibody production and inflammatory immune cells, which have been implicated in the development of RA. Both oral administration and intraperitoneal inoculation of L. helveticus SBT2171 reduced joint swelling, body weight loss, and the serum level of bovine type II collagen (CII)-specific antibodies in the CIA mouse model. The intraperitoneal inoculation also decreased the arthritis incidence, joint damage, and serum level of interleukin (IL)-6. In addition, the numbers of total immune cells, total B cells, germinal center B cells, and CD4+ T cells in the draining lymph nodes were decreased following intraperitoneal inoculation of L. helveticus SBT2171. These findings demonstrate the ability of L. helveticus SBT2171 to downregulate the abundance of immune cells and the subsequent production of CII-specific antibodies and IL-6, thereby suppressing the CIA symptoms, indicating its potential for use in the prevention of RA.